Structural and Mössbauer study of (Sb₀.₇₀Te₀.₃₀)₁₀₀-ₓ Snₓ alloys with x = 0, 2.5, 5.0 and 7.5 - Rocca, Javier Alejandro (2019)
(Sb₀.₇₀Te₀.₃₀)₁₀₀-ₓSnₓ alloys (with x = 0, 2.5, 5.0 and 7.5 at. %) have been synthesized and characterized in order to determine the crystalline structure and properties of materials obtained upon solidification and to extract information about the location of the Sn atom in the Sb-Te matrix. Powder X-ray diffraction (XRD) has been used to determine the crystalline structure, whereas Mössbauer spectroscopy has been utilized to determine the localization and the local structure of the Sn atom in the Sb-Te matrix through the hyperfine interactions of the ¹¹⁹Sn probe with its environment.We found that Sb₇₀Te₃₀ crystallizes in a trigonal structure belonging to P-3m1 space group, while the doping with Sn leads to structural distortions of the unit cell that can be described, for all the Sn concentrations, with the C2/m space group. The hyperfine parameters indicate that tin behaves as Sn(II) and has a slightly distorted environment. Finally, in order to extract all the information that the experimental results contain and to determine the preferential site occupied by the Sn impurities in the Sb-Te matrix, we have performed ab-initio calculations within the framework of the Density Functional Theory. The theoretical results enable us to determine the structural and electronic ground state of (Sb₀.₇₀Te₀.₃₀)₁₀₀-ₓSnₓ compounds and to confirm that Sn atoms substitute Sb atoms in the Sb-Te host.